School climate and attendance problems: the mediating role of student's academic and interpersonal competence - Luana Sorrenti; Concettina Caparello; Carmelo Francesco Meduri; Angelo Fumia; Pina Filippello (INFAD, 2024)
A positive school climate promotes regular attendance through strong relationships, a sense of belonging, diversity promotion, clear rules, and safety, leading to improved relational and educational outcomes. This study explores how perceived academic and interpersonal competence mediate the relationship between school climate components and absenteeism, using Havik’s(2015) model. A cross-sectionalstudy of 539 Italian high school students employed structural equation modelling with latent variables to examine these mediations. Results indicated that perceptions of interpersonal competence mediated the relationship between Peer Connectedness ( =.16,p<.01) and Affirming Diversity ( =-.05, p<.05) with Truancy. Perceived academic competence mediated the relationship between School Connectedness and Subjective Health ( =- .12, p<.01), Truancy ( =-.14, p<.01), andSchool Refusal ( =-.14, p<.01). The findings highlight the importance of promoting a positive school climate and enhancing students’ competences to reduce absenteeism.